Oral Presentation Performance, Self-Regulated Strategies and Perceived Challenges Among EFL Undergraduate Students in Samarinda - Anggraini, Rika; Jany Kalukar, Ventje; Parama Iswari, Weningtyas (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Limited research exists on oral presentation performance among EFL undergraduate students in Indonesian contexts, particularly regarding self-regulated strategies and perceived challenges. This study addresses the gap by examining presentation experiences across multiple institutions in Samarinda. This qualitative case study involved six sixth-semester students from English Education Departments at three universities: Mulawarman University, Universitas Muhammadiyah Kalimantan Timur, and Universitas Widya Gama Mahakam during 2022/2023. Data were collected through classroom observations, semi-structured interviews, and document analysis using purposive sampling. Miles and Huberman's analytical flow model was employed to identify patterns. Students demonstrated good presentation performance in content organization and visual aid utilization. Three challenge categories emerged: linguistic difficulties (grammar accuracy and vocabulary limitations), psychological barriers (presentation anxiety and confidence issues), and technical challenges (time management and organization). Cross-institutional analysis revealed distinct approaches: Mulawarman emphasized formal preparation, Widya Gama favored interactive methods, while UMKT focused on technology integration. Students employed effective self-regulated strategies including systematic practice with peer feedback, self-recording, anxiety management through breathing exercises, and structured organization using templates. Regular practice, thorough preparation, and appropriate anxiety management significantly improved performance outcomes. Findings support Krashen's Affective Filter Hypothesis and Oxford's language learning strategies. Pedagogical implications include incorporating anxiety management training, structured practice opportunities, technology integration, and differentiated instruction. This study uniquely examines cross-institutional differences in EFL presentation approaches within Indonesian university contexts, providing comprehensive insights into self-regulated strategies and perceived challenges specific to Samarinda's educational environment